Nurturing the Dispositions and Identities for Student Teachers’ Professional Development: A Critical Review - Frank Mwamakula (RIRAI Publisher, 2023)
This paper gives a critical review of studies centered on nurturing teachers’ dispositions, which is a pivotal role to teacher educators when executing teacher preparation programs and teacher development. Basing on experiential evidence, pre-service teachers are said to have higher expectations during their enrollment into the teaching program on the goals to achieve and the kind of teacher they wish to be. However, during the process of learning to teach they usually face “reality shock” especially during their teaching practice where they are exposed to the actual school and classroom environment. The challenges encountered during teaching practice are said to have negative impact on their beliefs about the career which lowers their self-efficacy, hence leading to job attrition for some of them. The studies discuss issues related to theory and practice in preparing student teachers from their pre-service teaching to beginning teachers heading to their on job professional development. Teaching profession is not that much smooth and easy task but a complex and dynamic task of knowing the learners’ expectations, differences and backgrounds and facilitating learning to suit the community’s context. Thus, student teachers require well informed and careful training and ongoing professional development which will enhance their beliefs, self-efficacy and identities and make teaching a productive endeavor.